Immunomodulatory therapies for autoimmune diseases - SULAIMANI, JAMAL (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
Multiple sclerosis (MS) and psoriasis are both T cell mediated autoimmune diseases that are triggered in genetically susceptible individuals in response to environmental factors. Th17 cells are strongly implicated in the pathogenesis of both MS and psoriasis, whereas Treg cells suppress effector T cell responses and prevent autoimmunity, however, their function has been shown to be impaired in both diseases. Therefore, targeting the Treg:Th17 axis is of great therapeutic interest in such autoimmune diseases. Therapies for both MS and psoriasis include a range of biologics or small molecules, some of which have very specific mechanisms of action whereas others have broader and less well understood mechanisms of action. Unfortunately most of these therapies can be associated with undesirable side effects and not all patients respond to treatment. Therefore, there is a need for safer therapies and a better understanding of the mechanisms of action of existing therapies. It has been established that vitamin D can exert anti-inflammatory effects in vitro and in vivo in the animal model for MS, prompting the idea of testing oral vitamin D3 supplementation as a therapy for MS. Vitamin D3 is an attractive therapy as it is safe and taken orally, however its efficacy in MS has not yet been established. A double-blind placebo-controlled randomised trial was conducted to examine the immunomodulatory effects of vitamin D3 in healthy controls (HC) (n=38) and clinically isolated syndrome (CIS) patients (n=29). CIS patients, who are those who have experienced only a single clinical neurological episode, were selected since they do not qualify for standard therapies, allowing for the effects of vitamin D3 supplementation to be assessed in isolation. However, although vitamin D3 supplementation increased serum 25(OH)D from baseline in both HC and CIS patients, no clinical or immunomodulatory effects on T cell subsets were observed and the trial did not meet its endpoints. Dimethyl fumarate (DMF) is the active ingredient in Fumaderm™, an oral drug which is used for the treatment of psoriasis, and DMF is now also used to treat MS. However, there is a need to better understand the mechanism of action of DMF both in vitro, and in vivo in psoriasis patients since it is poorly understood. Thus, the immunomodulatory effects of both vitamin D3 and DMF were examined in this study. In vitro studies using DMF revealed that the oxidative stress induced by DMF provided a relative advantage to Treg cells via their increased ability to resist oxidative stress. Furthermore, an increased frequency of Treg cells was also observed in psoriasis patients who had been treated with Fumaderm™, and this was associated with a significant decrease in memory CD4+ T cells and more specifically Th17 lineage cells. In summary, this study has provided useful information on the safety and dosage of vitamin D3 supplementation, but could not demonstrate clinical efficacy or immunomodulatory effects on T cell subsets. However this study has provided novel insights into the mechanism of action of DMF in vitro and in vivo, demonstrating that DMF modulated the Treg:Th17 axis in favour of Treg cells both in vitro and in vivo in psoriasis patients treated with Fumaderm™.
APPROVED
Keywords: Autoimmunity, Multiple Sclerosis, Psoriasis, Th17, vitamin D, Fumaderm, dimethyl fumarate